Kinerja keuangan sebelum dan selama pandemi Covid-19 perusahan subsektor Telekomunikasi - Lisa Erfina Yunita; Siti Mutmainah (Owner : Riset dan Jurnal Akuntansi, 2023)
The spread of the Covid-19 pandemic had an impact on all community activities from the educational, health, and economic aspects. Restrictions on activities imposed by the governments of various countries have reduced the volume of sales and production of business companies which had an impact on the company's financial performance. The purpose of the research is to analyze how significant the difference is in the financial performance of telecommunications sub-sector companies listed on the Indonesia Stock Exchange between before and during the covid-19 pandemic. This study uses the telecommunications subsector because, during the covid-19 pandemic, the industry has been considered to have a positive impact, but not all of them experienced positive financial growth. The measured financial performance includes profitability, liquidity, and solvency. The population consists of all telecommunications sector companies listed on the Indonesia Stock Exchange. The number of samples in this study is 19 telecommunications sub-sector companies consecutively for the 2018-2021 with saturated sampling technique. This type of research is is a descriptive quantitative study using a paired sample t-test. The findings show that the company's profitability and solvency before and during the Covid-19 pandemic experienced significant decrease. However, the company's liquidity did not change significantly during that time